The effects of being habitually barefoot on foot mechanics and motor performance in children and adolescents aged 6–18 years: study protocol for a multicenter cross-sectional study (Barefoot LIFE project) - Hollander, Karsten (J Foot Ankle Res, 2016)
BACKGROUND: Barefoot locomotion has evoked an increasing scientific interest with a controversial debate about benefits and limitations of barefoot and simulated barefoot walking and running. While most current knowledge comes from cross sectional laboratory studies, the evolutionary perspective suggests the importance of investigating the long-term effects. Observing habitually barefoot populations could fill the current gap of missing high quality longitudinal studies. Therefore, the study described in this design paper aims to investigate the effects of being habitually barefoot on foot mechanics and motor performance of children and adolescents. METHODS: This study has a cross-sectional, binational design and is part of the “Barefoot Locomotion for Individual Foot- and health Enhancement (Barefoot LIFE)” project. Two large cohorts (n((total)) = 520) of healthy children and adolescents between 6 and 18 years of age will be included respectively in Germany and South Africa. A barefoot questionnaire will be used to determine habitually barefoot individuals. The testing will be school-based and include foot mechanical (static arch height index, dynamic arch index, foot pliability) and motor performance (coordination, speed, leg power) outcomes. Gender, BMI and level of physical activity will be considered for confounding. DISCUSSION: The strength of this study is the comparison of two large cohorts with different footwear habits to determine long-term effects of being habitually barefoot on foot mechanics and motor performance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13047-016-0166-1) contains supplementary material, which is available to authorized users.